Good Practice of Educational Leadership to Succeed in The School Literacy Movement - Suriagiri Suriagiri (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Leadership in an institution is very important to achieve success in an institution, including leadership in education. This study aims to determine educational leadership that is considered ideal so that it not only improves the quality of education but can also achieve the level of success of the school literacy movement. The research method used in this research is qualitative with a literature review. The literature used is national, and international journals, books, documents, and other literature related to this research study. The findings of this study indicate that; First, to improve the quality of education, ideal leadership is needed, so that good relations between superiors and subordinates can improve the quality of education in the educational institutions that are led. Second, ideal leadership is also so that there is harmonization between superiors and subordinates so that the teaching and learning process is not pursuing achievement but teach according to the profession so that it can improve the literacy of students in schools.